Risk factors associated with early variceal rebleed after endoscopic variceal band ligation in cirrhotic Hepatitis B and C patients with variceal bleed: Risk factors associated with early rebleed in cirrhotic patients - Nasrullah, Atif; Kashif, Muhammad; Nasrullah, Haris; Saddiqiui, Arif Mahmood (Journal of Fatima Jinnah Medical University, 2020)
Background: Chronic liver disease is endemic in Pakistan with esophageal variceal bleeding as one of the important complications and is treated with EVBL. The early esophageal variceal rebleeding is one of the ignored factors which carries the high mortality and morbidity. Patients and methods: This case-control study was conducted in the Gastroenterology Department at Jinnah Hospital, Lahore, from February 2016 to February 2017. The Study included total 100 patients and out of these 50 were rebleeding cases while 50 were controls (without esophageal rebleed). Cases and control were matched for age, sex, Presence of hepatitis B and C and cirrhosis. The endoscopic findings of any active bleed and white nipple sign was recorded. Results: In this study, association of risk factors for prediction of early variceal rebleed after banding in cirrhotic hepatitis b and c patients with variceal bleed was recorded as 58%(n=29) in cases and 12%(n=6) for active bleeding, O.R was 10.12, 68%(n=34) in cases and 14%(n=7) in controls had nipple sign, O.R was 13.05, Hb level <9 g/dl was recorded in 88%(n=44) in cases and 40%(n=20) in controls, O.R 11.00, PT>18 sec was recorded in 96%(n=48) in cases and 4%(n=2) in controls, O.R was 576.00. Conclusion: Active bleeding and nipple sign, Hb level < 9 g/dl and PT > 18 sec are found to have strong association for prediction of early variceal rebleed after EVBL in cirrhotic hepatitis B and C patients.